Examining the mental health outcomes of peer-led school-based interventions on young people aged between 4 and 18 years old: a systematic review protocol - King, T; Fazel, M (BioMed Central, 2019)
Background: Recent estimates suggest that one in ten young people worldwide experiences a diagnosable mental health disorder, with many more suffering subsyndromal levels of psychological distress. As young people spend much of their time in schools, the role of educational settings in the delivery of mental health provision is increasingly recognised. Advances in neurodevelopmental research have highlighted the important and complex role of peer influence on adolescent behaviours, suggesting peer-led support schemes have high potential utility. Schools worldwide have implemented peer-led interventions with mixed results, but the global evidence base on their effectiveness remains limited. This systematic review aims to examine the evidence base of the outcomes of school-based peer-led interventions on the mental health of young people aged 4–18. Methods: Eligible studies will be randomised controlled trials and observational studies that report on the mental health outcomes of a peer-led school-based intervention. Eligible participants will be aged 4–18 and will be current students of the intervention school. Individual- and group-based interventions will be included. The following 11 databases will be screened based upon their reach in healthcare and education: PsycINFO, MEDLINE, EMBASE, CINAHL, CENTRAL, BEI, Scopus, Web of Science, ERIC, SSCI and Social Care Online. There will be no restriction placed on publication period, original language or country of publication. Papers will be systematically screened for eligibility by two review authors. Data will be presented as a descriptive report. A meta-analysis will be carried out if a subset of studies allows, given the anticipated high levels of heterogeneity. Discussion: This systematic review will be the first to synthesise the global evidence on the mental health outcomes of peer-led interventions for children and adolescents in a school setting. It will analyse the available data in order to understand the role of these interventions in schools, inform future developers of peer support programmes and identify gaps in current research. This review will be of value to policy makers, health and education services, researchers and those involved in delivering peer support initiatives.